Screening Of Okra Cultivars For Resistance Against Powdery Mildew Disease Caused By Erysiphae Cichoracearum (Journal of Plant Disease Sciences, 2020)
Field trial was conducted to screen the okra genotypes for determination of resistance against powdery mildew disease caused by Erysiphae cichoracearum. Among the 20 genotypes evaluated for resistance against powdery mildew disease, none of genotypes was found immune or resistant, while seven genotypes exhibited moderately resistant/ tolerant reaction and remaining 13 genotypes exhibited susceptible reaction to powdery mildew. Apparent rate of infection varied and at times they did not remain consistent for given genotype and also did not show a particular trend which is attributed to genetic character of the genotype. The AUDPC values differed considerably for different genotypes. The values of AUDPC and apparent rate of infection (r) of susceptible varieties were more comparable in moderately susceptible varieties. Genotype GK-IV-2-2-3 and Hissar Unnat having minimum AUDPC and apparent rate of infection value showed lowest intensity of powdery mildew while, genotype Pusa Sawani having maximum AUDPC and apparent rate of infection value showed highest intensity of powdery mildew disease on okra.
Keywords: Okra; Powdery mildew; Resistance; AUDPC